2014
DOI: 10.1111/sjpe.12049
|View full text |Cite
|
Sign up to set email alerts
|

Business Cycle Synchronization in EU: A Time‐Varying Approach

Abstract: This article investigates the time‐varying correlation between the EU12‐wide business cycle and the initial EU12 member‐countries based on Scalar‐BEKK and multivariate Riskmetrics model frameworks for the period 1980–2012. The paper provides evidence that changes in the business cycle synchronization correspond to major economic events that have taken place at a European level. In the main, business cycle synchronization until 2007 had moved in a direction positive for the operation of a single currency, sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
32
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 57 publications
10
32
2
2
Order By: Relevance
“…The process of higher synchronization between the two clusters has come to a hold shortly before the beginning of the financial crisis and consequently before the eruption of the sovereign debt crisis, thus corroborating the findings of Ferroni and Klaus (2015) in the case of Spain. Our findings are also in line with Degiannakis et al (2014) who suggest a general reduction in the co-movement of economic output among peripheral economies and the EMU-12 cycle after 2007.…”
Section: Local Polynomial Regressionssupporting
confidence: 81%
See 1 more Smart Citation
“…The process of higher synchronization between the two clusters has come to a hold shortly before the beginning of the financial crisis and consequently before the eruption of the sovereign debt crisis, thus corroborating the findings of Ferroni and Klaus (2015) in the case of Spain. Our findings are also in line with Degiannakis et al (2014) who suggest a general reduction in the co-movement of economic output among peripheral economies and the EMU-12 cycle after 2007.…”
Section: Local Polynomial Regressionssupporting
confidence: 81%
“…Thus, our quarterly correlation index and the LPR framework permit us to specifically track the changing relationship over time. Since our empirical investigation covers the time period from 1970Q1 to 2015Q4, we are able to investigate the potential (de)synchronizing effects of both the great financial crisis and the subsequent sovereign debt crisis, an issue that only a limited number of studies have addressed so far (Grigoraş and Stanciu, 2016;Degiannakis et al, 2014). Apart from the synchronization of business cycles, we also study their amplitudes because different amplitudes can lead to diverging cyclical conditions even if the cycles are perfectly correlated.…”
Section: Introductionmentioning
confidence: 99%
“…The interpretation is that the EMU, by favouring trade and integration of financial markets, has induced more similarity and synchronisation of shocks in the euro area. Despite this, our analysis also shows that some members appear to be latecomers in the process of integration, and that business cycles synchronisation has not increased considerably (Degiannakis et al, 2014).…”
Section: Discussionmentioning
confidence: 83%
“…Dynamic business cycle synchronization (BCS ij,t ) can be approximated by the time‐varying correlation level between two countries’ cyclical components. Recent studies in this strand of the literature have shown that multivariate GARCH models, such as the Baba, Engle, Kraft and Kroner (BEKK) model of Engle and Kroner () are successful in capturing the time‐varying synchronization, as this is approximated by the dynamic correlations (see, Degiannakis et al, ; Degiannakis et al, ). Given the low frequency of our data, and the relatively small time period, we use a more parsimonious version of the BEKK model, namely the Diagonal BEKK (Diag‐BEKK) model, as used by Degiannakis et al ().…”
Section: Data and Methods Descriptionmentioning
confidence: 99%
“…A vast amount of research has focused on business cycle synchronization and its determinants. Belke, Domnick, and Gros () provide an extensive review of the literature, along with the earlier research by Degiannakis et al (), Papageorgiou, Michaelides, and Milios (), de Haan, Inklaar, and Jong‐A‐Pin () and Altavilla (). The aim of the present study is not to present a thorough account of the existing findings, but rather to identify relevant gaps in the literature so to highlight the contribution made.…”
Section: Introductionmentioning
confidence: 99%